Effects of a Community-Based Multicomponent Positive Psychology Intervention on Mental Health of Rural Adults in Ghana - Appiah, R.; Wilson-Fadiji, A.; Schutte, L.; Wissing, M.P. (Applied Psychology: Health And Well-Being, 2020)
There is growing evidence that positive psychology interventions (PPIs) enhance positive mental health and lead to a decrease in symptoms of psychopathology. This study examines the effectiveness of a 10-week multicomponent PPI (the Inspired Life Program; ILP) in promoting positive mental health and reducing symptoms of depression and negative affect in a sample of rural poor adults in Ghana. Methods: Using a quasi-randomized controlled trial design, participants from four rural poor communities were randomly allocated to intervention (n = 40) or control (n = 42) conditions. The intervention group participated in the 10-week ILP. Both groups completed a battery of mental health measures, including the Mental Health Continuum-Short Form, at pre-intervention, immediately after the intervention, and at 3 months follow-up. Hierarchical linear modeling was applied to evaluate whether the intervention was effective. Results: There was a greater improvement in positive mental health, with a marked reduction in symptoms of depression in the intervention group compared to the control group, immediately and 3 months after the intervention. There were also larger increases in the proportion of flourishers in the intervention group compared to the control group, immediately and three months after the intervention. Conclusions: The observed effects of the ILP intervention program suggest that group-based PPIs can promote positive mental health and buffer against psychopathology among people living in rural poor communities in sub-Saharan Africa
Research Article
Keywords: community-based mental health intervention; Ghana; inspired life program; positive psychology intervention; quasi-randomized controlled trial; rural poor adults